(untitled) (Applied Biological Research, 2017)
Plants generally have medicinal value based on the kind and concentration of secondary metabolites they possess. One of such medicinally important plant Gymnema sylvestre R.Br. (Aslepiadaceae), commonly called ‘gurmar’, has widely been used in ayurvedic and homoepathic systems of medicine. Traditionally, this plant is used for its anti-diabetic potential attributed to the saponin named as gymnemic acid (Min et al., 2007). The nitrogen concentration in medium greatly influences the amount of secondary metabolite produced (Nagella and Murthy, 2011) as it is required for the expression of specific proteins (Sugiharto and Sugiyama, 1992). The NH4+ to NO3- ratio influences the amount of biomass produced (Nagella and Murthy, 2011). Secondary metabolites are accumulated in cells in response to biotic and abiotic stress. Proline is one of the compounds accumulated in response to stress (Yaish, 2015). The present study aimed to analyze the influence of nitrogen on biomass and total saponin production in G. sylvestre, through a cost